Menieroclerus gen. nov.: A new genus for Thanasimodes nigropiceus (Kuwert, 1893) (Coleoptera: Cleridae: Clerinae) - Bartlett, Justin S.; Gerstmeier, Roland (Zootaxa, 2016)
Opilo nigropiceus Kuwert was described from a specimen collected in Bagamoyo on the north coast of Tanzania, though the description was devoid of informative morphological detail (Kuwert 1893). Without comment, Schenkling (1915) transferred O. nigropiceus to Thanasimodes Murray, a genus erected by Murray (1867) for a single specimen from ‘Old Calabar’ (south Nigeria) described as Thanasimodes metallicus Murray. Thanasimodes presently contains ten species and is distributed widely throughout Africa, from South Africa to the northernmost countries (Corporaal 1950; Gerstmeier 1998).